Facile synthesis of N-doped TiO2 nanoparticles caged in MIL-100(Fe) for photocatalytic degradation of organic dyes under visible light irradiation. Issue 3 (June 2017) - Huang, Jie; Song, Haiyan; Chen, Chunxia; Yang, Yi; Xu, Ningdi; Ji, Xinzhen; Li, Chunyu; You, Jiang-An
Graphical abstract: Two-step synthesis of N-doped TiO2 nanoparticles caged in MIL-100(Fe) as efficient photocatalyst. Highlights: Convenient synthesis of MIL-100(Fe) caging N-doped TiO2 nanoparticles. Size of N-TiO2 particles in MIL-100(Fe) cages at quantum dots scale. Enhanced photocatalytic performance for dyes degradation over N-TiO2 /MIL-100(Fe). N-TiO2 /MIL-100(Fe) avoids agglomeration and difficult separation of free TiO2 particles. Abstract: A metal-organic frameworks (MOFs) matrix of MIL-100(Fe) loading N-doped TiO2 (N-TiO2 ) nanoparticles as a novel photocatalyst was successfully synthesized by a facile two-step strategy including preparation of neutral N-TiO2 sol and caging N-TiO2 nanoparticles. The as-synthesized samples were characterized by a series of techniques including XRD, ICP, BET, UV–vis, XPS and TEM. Photocatalytic activity of the samples was assessed based on degradation of methylene blue or rhodamine B dye in model wastewater under visible-light irradiation. The as-synthesized samples essentially maintain the typical MOFs structure and porous property of MIL-100(Fe), which exhibits well confinement effect on TiO2 nanoparticles. A significant finding is that the quantum dots-like N-TiO2 nanoparticles (<2 nm) with an appropriate mass percentage of 32% highly disperse in cages of MIL-100(Fe) with 1.9 nm of pore size and obtain narrowed band gap. But agglomeration of N-TiO2 nanoparticles occurs as TiO2 content increases to 50%. Meanwhile, nitrogen atoms are successfully incorporated into the TiO2 lattice. The optimal catalyst obtains 99.1% and 93.5% of final removal rate, respectively for methylene blue and rhodamine B, presenting the enhanced photocatalytic performance by comparison with the pure MIL-100(Fe). The composite exhibits more excellent sedimentation efficiency and reusability than pure N-TiO2 . A possible mechanism of the photocatalysis process is presented in detail.